CARCASS AND NON CARCASS PERCENTAGES OF 35 DAY-OLD MALE QUAILS (COTURNIX-COTURNIX JAPONICA) GIVEN DRINK CONTAINING MORINGA LEAF SOLUTION - fitrah, halim; Handarini, Ristika; Dihansih, Elis (Jurnal Peternakan Nusantara, 2018)
Quail is potential to provide protein source but its meat production in Indonesia is still limited.  Thi study was aimed at assessing the effects of the inclusion of moringa leaf solution in dringking water on carcass and giblet percentages of quails.  The study was conducted at Badrupuyuh Farm, Sukajaya Village RT 01/02, Ciomas, Bogor Regency from October to December 2017.  One-hundred quail birds aged 7 days with average initial body weight of 18.04±0.508 g were used.  The birds were fed starter and grower commercial rations.  Moringa leaf solution was given through drinking water.  A completely randomized design with 4 treatments and 5 replicates was used.   Treatments consisted of drinking water containing no moringa leaf solution (R0), drinking water containing 5% moringa leaf solution (R1), drinking water containing 10% moringa leaf solution (R2), drinking water containing 15% moringa leaf solution (R3).  Data were subjected to an analysis of variance and a Duncan test. Measurements were taken on the percentage of carcass, liver, gizzard, and heart. Results showed that treatments gave significant effects on liver percentage but not on the percentages of carcass, heart, and gizzard.  It was concluded that the inclusion of moringa leaf solution of up to 10% in drinking water optimized carcass and non carcass percentages of male quails.  It was recommended that moringa leaf solution of up to10% be included in drinking water of male quails. Key words: male quail, carcass, giblet, moringa leaf solution.